Implementation of Compensation Payments for Land in Siak Regency Based on Law Number 2 of 2012 Concerning Land Acquisition for Development for Public Interest - Jekson Sihombing; Sriono Sriono; Wahyu Simon Tampubolon (Journal of Social Research, 2023)
Soil is an important aspect of human life, having a role in the main foundation of all life carried out by man. This study aims to determine and analyze the implementation of compensation payments for land based on law number 2 of 2012 concerning land acquisition for development for the public interest. As well as knowing and analyzing obstacles to the implementation of compensation payments on land based on law number 2 of 2012 concerning land acquisition for development for the public interest. This research belongs to the normative type of research. So it can be known that these stages are planning, preparation, implementation, and submission of results. In addition, the process of providing compensation for land-owning communities must be carried out optimally, even the determination of the amount of compensation value must be carried out evenly.